Livelihood risk from HIV in semi-arid tropics of rural Andhra Pradesh - B. Valentine Joseph Gandhi; M. Cynthia Serqui\~na Bantilan; Devanathan Parthasarathy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper discusses the livelihood dynamics in the fragile landscape of the semi-arid tropics (SAT) of Andhra Pradesh. SAT is home to the poorest of the poor who live in conditions of persistent drought, subsistence agriculture and poor access to markets. This paper is a case study focusing particularly on labour migration, its role in influencing the health risk behaviour of migrants and in the spread of the HIV epidemic among SAT rural households. The most vulnerable population in these drought-prone regions are the migrant labourers, and their vulnerability is influenced by three major factors - the vulnerability and unstable productivity in the degraded and marginal landscape, the caste system that has traditionally kept them backward and vulnerable, and experiences in the external.
Keywords: I19; O5; Q19; 330; labour migration; HIV risk behaviour; agriculture; health; semi-arid tropics; Regionale Arbeitsmobilität; Migranten; Gesundheit; Ländlicher Raum; Trockenklima; Tropen; Andhra Pradesh